Clinical Efficacy of Extracorporeal Shock Wave in the Treatment of Knee Osteoarthritis： A Meta-analysis - GU Jinyu; LI Kaiming; ZHANG Qing; LI Linghui; BAI Zixing; WANG Shangquan (康复学报)
ObjectiveTo evaluate the efficacy and safety of extracorporeal shock wave therapy for knee osteoarthritis (KOA) by Meta analysis.MethodsThe CNKI database, Wanfang Data, China Science and Technology Journal Database (VIP), CBMdisc, PubMed and Cochrane Library were searched from inception to October 2020 for randomized controlled trials (RCTs) of extracorporeal shock wave therapy for KOA. Outcome measures included overall efficiency, visual analogue scale (VAS), Lequesne index score, Western Ontario and McMaster University Osteoarthritis Index score (WOMAC), and incidence of adverse reactions. Literature screening and data extraction were carried out independently by two researchers, and the literature quality was evaluated according to the Cochrane Collaboration Network standard. RevMan 5.3 software was used for data analysis. Relative risk (RR) was used to analyze the binary variables; and the continuous variables with the same unit and measurement method were described by mean difference (MD), while the continuous variables with different measurement methods or units were described by standardized mean difference (SMD). The random-effects model was used for analysis when the included studies were heterogeneous (I2≥50%, P<0.1), and the fixed effects model was used when the included studies were homogeneous (I2<50%, P>0.1).ResultsA total of 13 RCTs with 1 132 cases were included, 577 in the observation group and 555 in the control group. The results of meta-analysis showed that the overall efficiency of the observation group was significantly higher than that of the control group, and the difference was statistically significant [RR=1.13, 95% CI(1.05, 1.22), P=0.000 8]; the Lequesne index score of the observation group decreased more significantly after treatment than that of the control group, and the difference was statistically significant [SMD=0.68, 95% CI(0.47, 0.90), P<0.000 01]; the VAS scores of the observation group were significantly lower than those of the control group after 1, 2 and 3 months of treatment, and the differences were statistically significant (P<0.000 01); the decrease of WOMAC score in the observation group after 0.5, 1, 2 and 3 months treatment was more significantly than that of the control group (P<0.01); there was no significant difference in the incidence of adverse reactions between the two groups [RR=0.42, 95% CI(0.13, 1.33), P=0.14].ConclusionExtracorporeal shock wave therapy is safe and efficient in the treatment of patients with KOA, and is recommended for clinical application. Due to the quality limitations of the included studies, high-quality, multi-center RCTs with large sample size are still needed to verify the clinical effects in the future.